ANALISIS HUBUNGAN MOTIVASI KERJA DAN KOMUNIKASI TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA OGAN KOMERING ULU - Sarwo, Sri; Kasisariah, Tri Rusilawati; Iskandar, Iskandar (STMIK Pringsewu, 2024)
This study is based on factors that cannot be ignored related to employee job satisfaction at the Ogan Komering Ulu Human Resources Development and Personnel Agency, namely Work Motivation and Communication. This can be reflected in low job satisfaction because work motivation and communication between leaders and staff are still lacking, this can be seen from the discipline of working hours which is still far from what employees expect at the Ogan Komering Ulu Human Resources Development and Personnel Agency. The purpose of this study is first to determine the effect of work motivation on employee job satisfaction at the Ogan Komering Ulu Human Resources Development and Personnel Agency, second to determine the effect of communication on employee job satisfaction at the Ogan Komering Ulu Human Resources Development and Personnel Agency, third to determine the effect of work motivation and communication together affect employee job satisfaction at the Ogan Komering Ulu Human Resources Development and Personnel Agency.